Plagiarism: Types, Causes and How to Avoid This Worldwide Problem - Roka, Yam Bahadur (Nepal Journal of Neuroscience, 2017)
Publication in medical journals are important to help humans towards a healthier future and to disseminate knowledge regarding the pros and cons of any disease, treatment, drugs, research or other medical issues.There are many ways in which misconduct in medical research can be defined and the presence of thousands of journals worldwide and ease of access of these articles across the globe has not led to any common name to define this problem. There are many reasons for plagiarism starting from individual and not limiting to institutions, journals, textbooks, research funding agencies or international trials. Previously the only method to detect plagiarism was the ability/experience of the editor or reviewer to detect copies from the original. Newer and more sophisticated computer methods that analyze lexical, syntactic, and semantic features, tracking of paraphrasing, citation based detection, analyzing the graphics, cross language text borrowing by non-English speakers and copying of references will aid to detect plagiarism. Retraction of the article, blacklisting of the author with or without institution and expulsion from the institute, criminal charges, apology letter are some of the penalties for plagiarism. Nepal Journal of Neuroscience, Volume 14, Number 3, 2017, page: 2-6